MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI BANGUN RUANG MELALUI PROBLEM BASED LEARNING - Etik Djumiati; Sandha Soemantri; Sayyidati Marlinda Yunita (PROCEEDING UMSURABAYA, 2024)
This research aims to improve the mathematics learning outcomes of class 2A students of SD Negeri Ngagel Rejo 1/396 Surabaya for the 2022/2023 academic year through the application of the Problem-Based Learning model. This research involved 28 class 2A students with the type of Classroom Action Research (PTK) which was carried out for 2 cycles where each cycle was carried out in 1 meeting. Each cycle is carried out in 4 stages, namely planning, implementation, observation and reflection. Data were collected through evaluation tests of learning outcomes which were carried out at the end of each cycle and analyzed descriptively From the analysis of the data that has been done, it is found that the application of the Problem-Based Learning learning model can improve student learning outcomes. This can be seen from the average student learning outcomes in cycle 1 was 78. 9 with the percentage of students who completed KKTP was 79% and the average student learning outcomes in cycle 2 was 91, 42 with the percentage of students who completed KKTP is 91%. There was an increase in the average learning outcomes and the percentage of students who completed the KKTP.